A preparation method and application of Janus silicon quantum dots

Janus silicon quantum dots were prepared by one-step "green" synthesis method and Pickering emulsion method, and the modification of polypropylene glycol and bis-(3-(triethoxysilane)propyl)-disulfide was solved, and the stability of Janus nanomaterials under preparation below 10 nm and under high temperature and high salt environment was achieved, and the compatibility of high interfacial activity and dispersion stability was expanded, and its application potential in the field of colloid and interfacial chemistry was expanded.

CN118995203BActive Publication Date: 2025-04-25CHINA UNIV OF PETROLEUM (BEIJING)

Patent Information

Application Number
CN202411063525.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-04-25
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The prior art is difficult to prepare Janus nanomaterials below 10 nm and maintain monodispersion stability in high temperature and high salt environments, resulting in difficult compatibility of high interfacial activity and dispersion stability, which limits its development and application in the field of colloids and interfacial chemistry.

Method used

A one-step "green" synthesis method was used to prepare silicon quantum dots containing polyoxyethylene chain segments on the surface using silicon source containing polyethylene glycol, strong reducing agents and alkalis as raw materials. The preparation and half-plane hydrophobization of Janus silicon quantum dots were achieved through the Pickering emulsion method and the modification of polypropylene glycol and bis-(3-(triethoxysilane)propyl)-disulfide.

Benefits of technology

The preparation of Janus nanomaterials below 10nm was achieved, and monodispersion stability is maintained in high temperature and high salt environments, with high interfacial activity and dispersion stability, filling the research gap in Janus nanomaterials in quantum dot size and expanding its application potential in the field of colloids and interface chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118995203B_ABST
    Figure CN118995203B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of Janus silicon quantum dots. The Janus silicon quantum dots are prepared by combining a one-step "green" synthesis method with a Pickering emulsion method. First, poly(ethylene glycol) trimethoxysilyl propyl ether), sodium citrate and sodium hydroxide are used as raw materials to prepare silicon quantum dots (SiQDs) containing specific polyoxyethylene segments on the surface; then, the optimized Pickering emulsion method is used to half-face modify the silicon quantum dots, and polypropylene glycol and bis-(3-(triethoxysilane)propyl)-disulfide are used to treat the surface of the silicon quantum dots during the modification process. The Janus silicon quantum dots prepared by the present invention achieve a breakthrough in the scale of Janus nanomaterials, so that the size of Janus nanomaterials reaches less than 10nm; the Janus silicon quantum dots solve the problem of high interfacial activity and dispersion stability being difficult to be compatible through the design of special surface functional groups, and show good dispersion stability and high interfacial activity under harsh conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil field production, and relates to a preparation method and application of asymmetric silicon quantum dots, and specifically relates to a preparation method and application of Janus silicon quantum dots. Background Art

[0002] Janus nanoparticles are characterized by an asymmetric structure on their surface, with each hemisphere displaying different features. Such anisotropic nanoparticles have unique properties, including surface / interfacial activity, Janus nanomotors, controllable self-assembly, and medical applications. These properties offer significant benefits over isotropic nanoparticles. Among them, Janus nanoparticles can spontaneously adsorb on liquid / liquid and solid / liquid interfaces due to their high interfacial activity, thereby improving emulsion stability, reducing surface / interfacial tension, and promoting solid / liquid separation. However, the synthesis of amphiphilic Janus nanoparticles is limited by complex silicon surface chemistry. The preparation of amphiphilic Janus nanoparticles is limited to more than 10 nm, which limits their development and application in the field of colloid and interface chemistry. Due to their unique half-surface hydrophilic and half-surface hydrophobic configurations, amphiphilic Janus nanoparticles exhibit strong Brownian motion in water, which is an important factor for their spontaneous adsorption on interfaces, but also poses a challenge to maintaining their colloidal stability. In addition, as the particle size of Janus nanoparticles decreases, the increase in specific surface area and surface energy makes the particle agglomeration tendency more serious, which is a fatal problem that affects the performance of Janus nanoparticles with particle size dependence. At present, the mechanism behind the unique surface / interface phenomenon of Janus nanoparticles and the principle controlling their adsorption and diffusion are still unclear. Due to the difficulty in achieving high interfacial activity and dispersion stability at the same time, the application potential of Janus nanoparticles is greatly limited, which has greatly hindered the progress of many related research. Summary of the invention

[0003] Based on the problems existing in the prior art, the first purpose of the present invention is to provide a method for preparing Janus silicon quantum dots. The Janus silicon quantum dots prepared by the present invention realize the preparation of Janus nanomaterials below 10nm, and can achieve the monodispersity and stability of Janus silicon quantum dots in a high temperature and high salt environment, ensuring the high interfacial activity, achieving a breakthrough in the size of Janus nanomaterials, and solving the scientific problem that the high interfacial activity and dispersion stability of Janus nanomaterials are difficult to be compatible.

[0004] The method for preparing Janus silicon quantum dots provided by the present invention comprises the following steps:

[0005] 1) A one-step "green" synthesis method is used to prepare silicon quantum dots containing polyethylene glycol segments on the surface using a silicon source, a strong reducing agent, and a base as raw materials;

[0006] 2) mixing the obtained dispersion of silicon quantum dots containing polyoxyethylene segments with molten paraffin in water and stirring to obtain small paraffin balls coated with silicon quantum dots; wherein half of the silicon quantum dots are in contact with the small paraffin balls and the other half is exposed;

[0007] 3) using polypropylene glycol and bis-(3-(triethoxysilane)propyl)-disulfide to perform half-surface hydrophobic modification on silicon quantum dots, and after the modification is completed, demulsifying the paraffin emulsion and removing the paraffin under high temperature and high salt environment conditions;

[0008] 4) The system after removing the paraffin is dialyzed to obtain a Janus silicon quantum dot dispersion.

[0009] The operation of step 1) of the above method is: first, a strong reducing agent is added to deionized water, stirred to dissolve, a silicon source containing polyethylene glycol is added, stirred to mix, an alkaline solution is added to adjust the pH of the mixture to 8-8.5, the resulting mixture is reacted at 100-120° C., the product is dialyzed using a dialysis bag, and the resulting silicon quantum dot dispersion is evaporated and concentrated at high temperature to obtain a dispersion of silicon quantum dots containing polyethylene oxide segments on the surface;

[0010] The silicon source containing polyethylene glycol includes but is not limited to polyethylene glycol trimethoxysilyl propyl ether, polyethylene glycol triethoxysilyl propyl ether and polyethylene glycol trimethoxysilyl ethyl ether;

[0011] The strong reducing agent includes but is not limited to sodium citrate, sodium ascorbate, etc.;

[0012] The alkali includes but is not limited to sodium hydroxide, potassium hydroxide and calcium hydroxide;

[0013] The mass volume ratio of the base to the silicon source containing polyethylene glycol can be: 2.5-4g:10ml;

[0014] The reaction time is not less than 6 hours, specifically 6-12 hours;

[0015] The dialysis is performed for at least 48 hours;

[0016] The mass concentration of silicon quantum dots containing polyoxyethylene chain segments on the surface in the obtained dispersion of silicon quantum dots containing polyoxyethylene chain segments on the surface can be 10-20wt%.

[0017] In step 2) of the above method, the volume ratio of the dispersion of silicon quantum dots containing polyoxyethylene segments on the surface to the molten paraffin can be 8-12:1, specifically 10:1;

[0018] The stirring conditions may be: a stirring speed of 10000-12000 rpm, a stirring time of 5-15 min, and specifically stirring at 12000 rpm for 5 min;

[0019] For J-SiQDs, the Pickering emulsion method was used to modify the synthesis route of Janus silicon quantum dots, thereby realizing the preparation of Janus silicon quantum dots, considering the three key characteristics of poor interface adsorption of hydrophilic silicon quantum dots, strong stability of stable paraffin emulsion at high temperature, strong salt resistance, and small particle size of paraffin emulsion making it difficult to achieve centrifugal separation and suction filtration separation.

[0020] In step 3) of the above method, the pH value of the solution is first adjusted to 3.5-4.5, polypropylene glycol is added to the solution, and bis-(3-(triethoxysilane)propyl)-disulfide is added dropwise while stirring. After the addition is completed, the reaction is continued under stirring. After the reaction is completed, CaCl2 solution is added and heated to boil to fully precipitate the paraffin from the water, thereby achieving the removal of the paraffin.

[0021] Wherein, the Mw of polypropylene glycol is 600-1000, specifically 600;

[0022] The mass volume ratio of polypropylene glycol, bis-(3-(triethoxysilane)propyl)-disulfide and the silicon source containing polyethylene glycol in step 1) can be: 2-5g: 1-2g: 10-12ml, specifically 2-5g: 1g: 10ml, more specifically 2g: 1g: 10ml;

[0023] The process of adding bis-(3-(triethoxysilyl)propyl)-disulfide was continued for 3 h;

[0024] The reaction time under stirring can be 6-12 hours, specifically 12 hours;

[0025] The volume ratio of the CaCl2 solution (greater than or equal to 30000 mg / L) to the molten paraffin in step 2) can be 20-100 ml:5 ml, specifically 20 ml:5 ml;

[0026] Heat to 120℃ and boil for more than 3h.

[0027] In step 4) of the above method, the water is changed every 2 hours for the first three times during the dialysis process, and then every 6 hours for 48 hours to obtain a pure Janus silicon quantum dot dispersion.

[0028] The Janus silicon quantum dots (J-SiQDs) prepared by the above method also fall within the protection scope of the present invention.

[0029] The Janus silicon quantum dots (J-SiQDs) prepared by the present invention have a particle size of less than 10 nm, have high interface activity and dispersion stability.

[0030] The Janus silicon quantum dots exhibit good dispersion stability and strong interfacial activity under high temperature, high salt and wide pH range.

[0031] More specifically, at 120°C, Ca 2+ Under the conditions of a concentration of 50000 mg / L and pH=4-10, the Janus silicon quantum dot fluid exhibits good dispersion stability and strong interfacial activity in a concentration range of 0.005wt%-3.0wt%.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) Based on the Pickering emulsion method, a synthesis method suitable for quantum dots with smaller particle sizes was adopted. J-SiQDs with a particle size of about 5nm were obtained, thus solving the research gap of Janus nanoparticles below 10nm.

[0034] (2) The J-SiQDs prepared by the present invention can be used in a 3D image with a root mean square displacement of 149 cm 2 The monodispersed state can be maintained for more than 48 hours under the high interfacial activity state. It avoids the use of traditional chemical additives to maintain dispersion stability and achieves the compatibility of high interfacial activity and dispersion stability.

[0035] (3) At 120℃, Ca 2+ Under the harsh environmental conditions of a concentration of 50000 mg / L and pH=4-10, the prepared Janus silicon quantum dot fluid exhibits good dispersion stability and strong interfacial activity in a concentration range of 0.005wt%-3.0wt%.

[0036] The present invention takes into account the unique characteristics of SiQDs, such as small particle size and rich surface functional groups, and constructs amphiphilic Janus silicon quantum dots (J-SiQDs). This achievement fills the research gap in the size of Janus nanomaterials in quantum dots and contributes to the development of Janus nanomaterials. It is worth noting that it solves the scientific problem that the high interfacial activity and colloidal dispersion stability of Janus nanomaterials are difficult to be compatible. The colloidal dispersion stability of J-SiQDs under various harsh environmental conditions is further improved, thereby ensuring the optimal performance of J-SiQDs. In addition, J-SiQDs have shown great potential in many fields such as enhanced oil recovery, microelectronics, coatings and bioimaging. The performance of J-SiQDs is outstanding in its high interfacial activity, and its practical application depends on the key guarantee of colloidal dispersion stability. Therefore, the use of compatible J-SiQDs will expand the application range of Janus nanomaterials and promote the research of various optoelectronic and interface effect mechanisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the structure and synthesis route of Janus silicon quantum dots prepared in Example 1 of the present invention.

[0038] Figure 2 Characterization of the microscopic morphology and photoluminescence properties of SiQDs and J-SiQDs. (a) and (b) are transmission electron microscope images of SiQDs and J-SiQDs, (c) is a mechanism diagram of J-SiQDs maintaining monodisperse stability during drying, (d) is the particle size test results of SiQDs and J-SiQDs, (e) is the infrared spectrum test results of SiQDs and J-SiQDs, (f) and (g) are the excitation and emission spectra of SiQDs, (h) and (i) are the excitation and emission spectra of J-SiQDs, and (j) is a mechanism diagram of the change of photoluminescence properties of J-SiQDs.

[0039] Figure 3 The interface phenomena of SiQDs with different surface structures. (a) shows the adsorption of amphiphilic J-SiQDs at the oil-water interface, (b) shows the stable dispersion of SiQDs in water, (c) shows the lack of obvious adsorption of SiQDs at the oil-water interface, and (d) shows the climbing of amphiphilic J-SiQDs along the interface between the glass phase and the oil phase.

[0040] Figure 4Characterization of the interfacial activity and dispersion stability of J-SiQDs. (a) is the MSD curve of SiQDs, (b) is the MSD curve of amphiphilic J-SiQDs, (c) is the particle size measurement of J-SiQDs before and after standing for 48 hours, (d) is the TSI data of amphiphilic J-SiQDs, (e) is the transmission light intensity change image of SiQDs, and (f) is the transmission light intensity change image of J-SiQDs.

[0041] Figure 5 Schematic diagram of the dispersion stability mechanism of J-SiQDs. (a) is the source of the repulsive force between J-SiQDs particles, and (b) is the spontaneous adsorption mechanism of J-SiQDs at the oil-water interface.

[0042] Figure 6 Molecular dynamics simulation of J-SiQDs. (a) is the simulation of the stable existence of J-SiQDs in water, (b) is the schematic diagram of the microstructure of steady-state J-SiQDs, (c) is the simulation of the spontaneous adsorption properties of J-SiQDs at the oil-water interface, (d) is the simulation of the collision and separation process of J-SiQDs, and (e) is the simulation of the distance between J-SiQDs changing with time within 3ns.

[0043] Figure 7 (a) is the photoluminescence phenomenon of SiQDs. Figure 7 (b) is the photoluminescence phenomenon of J-SiQDs. Figure 7 (c) shows the phenomenon of ultraviolet irradiation on deionized water.

[0044] Figure 8 Characterization of the dispersibility and stability of J-SiQDs under different conditions. (a), (c), (e), and (g) are the particle size test results of J-SiQDs at different concentrations, salinities, temperatures, and pH values, respectively; (b), (d), (f), and (h) are the stability test results of J-SiQDs at different concentrations, salinities, temperatures, and pH values, respectively. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0046] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0047] Example 1

[0048] This embodiment provides a method for preparing amphiphilic Janus silicon quantum dots. The synthesis process of Janus silicon quantum dots is as follows: Figure 1 As shown, the specific steps include:

[0049] Step 1: First, add 2.78g of sodium citrate to 30ml of deionized water and stir to dissolve. Then add 10ml of polyethylene glycol trimethoxysilyl propyl ether to the solution and stir to mix. Then adjust the pH of the mixture to 8 with 0.1mol / LNaOH solution. The mixture is reacted in one step at 120°C for 6h. The product is dialyzed using a dialysis bag for 48h. The obtained silicon quantum dot dispersion is evaporated and concentrated to a concentration of 20wt%.

[0050] Step 2: For J-SiQDs, considering the three key characteristics of poor interface adsorption of hydrophilic silicon quantum dots, strong stability of stable paraffin emulsion at high temperature, strong salt resistance, and small particle size of paraffin emulsion, which makes centrifugal separation and suction filtration separation difficult, the synthesis route of Janus silicon quantum dots was modified by Pickering emulsion method, thereby realizing the preparation of Janus silicon quantum dots. 50ml SiQDs dispersion and 5ml paraffin were stirred in water at 12000rpm for 5min to prepare small paraffin balls coated with SiQDs.

[0051] Step 3: Adjust the pH of the solution to 4. Then add 2g of polypropylene glycol (Mw: 600) to the dispersion and stir for 10 minutes to fully dissolve. While stirring, add 1g of bis-(3-(triethoxysilane)propyl)-disulfide (bis-(3-triethoxysilanepropyl)-disulfide) dropwise until all is completed, which takes about 3 hours, and then continue stirring for 12 hours. After the reaction is completed, add 20ml of CaCl2 solution (30000mg / L), heat to 120℃ and boil for 3 hours to fully precipitate the paraffin from the water and achieve the removal of the paraffin.

[0052] Step 4: The prepared Janus silicon quantum dots were dialyzed twice. The water was changed every 2 hours for the first three times during the dialysis process, and then every 6 hours for 48 hours to obtain a pure Janus silicon quantum dot dispersion.

[0053] Example 2

[0054] The morphology of SiQDs before and after surface treatment was characterized by high-resolution transmission electron microscopy (FEI Tecnai G2 F30, USA). Figure 2As shown in Figure a, the microscopic morphology of SiQDs and J-SiQDs is characterized. As can be seen from the figure, the particle size of SiQDs is about 3nm. SiQDs are in a monodisperse state without obvious agglomeration, which is conducive to the preparation of nanofluids. The microscopic morphology of amphiphilic J-SiQDs is shown in Figure 2 b. After surface modification, the particle size of J-SiQDs increased significantly to about 5 nm. It is particularly noteworthy that the amphiphilic J-SiQDs continue to be monodisperse. The present invention achieves the maintenance of monodispersity under drying conditions by grafting specific functional groups on the hydrophobic half of the J-SiQDs. During the drying process of J-SiQDs, the surface organic segments consistently show a tendency to bind to water molecules rather than to bind to organic segments on other J-SiQDs, such as Figure 2 This situation remains the same as the number of water molecules decreases (c).

[0055] The particle size distribution of SiQDs and J-SiQDs was measured using a laser particle size analyzer (Malvern Instruments Ltd., UK). Figure 2 The particle size of SiQDs and J-SiQDs in deionized water measured by a nano-laser particle size analyzer is shown in Figure d. The experimental results show that the particle size of J-SiQDs is slightly larger than that of SiQDs due to the addition of additional functional groups on the hydrophobic semi-surface. The particle size of J-SiQDs is about 5.2nm±0.2nm.

[0056] Fourier transform infrared spectroscopy (FT-IR) was used to characterize the characteristic functional groups of SiQDs before and after modification. Figure 2 Figure e is the infrared spectrum test results of SiQDs and J-SiQDs. The two substances have an infrared spectrum of 3353 cm -1 The vibration peak at 2938cm is caused by the stretching vibration of -OH. From the chemical structures of the two, it can be seen that there are still a large number of hydroxyl groups on the surface of silicon quantum dots before and after modification. -1 and 2863cm -1 The stretching vibration peak at 1105cm -1 The peak at 563cm is mainly derived from the stretching vibration of -CO-, which is present in large quantities on the surface of SiQDs and in the subsequently grafted polyacryl alcohol segments. -1 The absorption peak at is the characteristic peak of J-SiQDs, which is caused by the stretching vibration of -SS-. The presence of this functional group is an important sign of successful modification.

[0057] The excitation and emission wavelengths before and after modification were characterized using a steady-state-transient fluorescence spectrometer (FLS1000, UK). Figure 2 Figure 1 shows the excitation and emission spectra of SiQDs and amphiphilic J-SiQDs. After semi-surface modification, the excitation spectrum of SiQDs dropped from about 440nm to 355nm, and the emission spectrum dropped from about 330nm to 280nm. Due to the change of surface chemical segments, the changes in the excitation and emission spectra of SiQDs further illustrate the successful grafting of surface chemical segments. The luminescence phenomenon of SiQDs and J-SiQDs under 345nm ultraviolet light is shown in Figure 1. Figure 7 .

[0058] The change in the photoluminescence properties of J-SiQDs may be related to its anisotropic structure. In the surface state luminescence model of silicon quantum dots, the photoluminescence properties of silicon quantum dots are significantly affected by the type of surface groups. By manipulating the surface structure of silicon quantum dots, their photoluminescence peak can be adjusted in the visible spectrum. From the photoluminescence mechanism of SiQDs, the photoluminescence characteristics of J-SiQDs can be explained by the charge transfer process promoted by the surface groups. The presence of different functional groups on the hydrophilic and hydrophobic parts of J-SiQDs can lead to different photoluminescence capabilities. This leads to an overall change in the photoluminescence effect, such as Figure 2 As shown in Figure 5.

[0059] It is worth noting that since the particle size of J-SiQDs is less than 10 nm, it is impossible to visually distinguish them by fluorescence imaging, so we used an indirect method to characterize their specific structure. The amphiphilicity of SiQDs was confirmed by observing the spontaneous adsorption of SiQDs on the oil (n-heptane) / water interface and the climbing behavior of the solid / liquid interface. Figure 3 In a, J-SiQDs aqueous dispersion system and n-heptane were included. It was observed that J-SiQDs formed an obvious adsorption layer at the oil-water interface, and they climbed along the interface between the glass bottle and the oil phase ( Figure 3 (d) Figure 3 Figure b shows hydrophilic SiQDs. SiQDs are stably dispersed in aqueous solution and do not exhibit adsorption behavior at the oil-water interface, nor do they exhibit solid-liquid interface climbing due to structural separation pressure ( Figure 3 (c) The prepared J-SiQDs behave in accordance with other anisotropic amphiphilic nanoparticles, and this behavior is generally considered to have achieved the preparation of J-SiQDs.

[0060] The spontaneous adsorption of J-SiQDs at the oil-water interface is due to its special structure of half hydrophilic and half oleophilic. The Janus structure enhances the intensity of its Brownian motion in water, increases its adsorption energy at the oil-water interface, and keeps J-SiQDs stable at the interface. J-SiQDs can significantly reduce the oil-water interfacial tension and improve wettability. As a result, the shape and structure of the oil-water interface change. Since the particle size of J-SiQDs is small and the dispersibility at the oil-water interface is affected by the interfacial tension, J-SiQDs will be closer to the oil / water / solid three-phase contact angle. The thinner the nanoparticle layer is, the closer the distance to the three-phase contact angle is, and the structural separation pressure will increase significantly. This causes the oil phase to peel off from the solid surface and J-SiQDs to climb along the oil-solid interface. The successful preparation of J-SiQDs is of great significance to the development of relevant theories in the field of colloid and interface chemistry.

[0061] Example 3

[0062] The interfacial activity and dispersion stability of J-SiQDs were studied using an optical microrheological analyzer, a multiple light scattering instrument, and a laser particle size analyzer. The root mean square displacement curve (MSD curve) was used to determine the Brownian motion intensity of J-SiQDs and determine its spontaneous adsorption performance at the oil-water interface. Combined with the particle size test results, the Turbiscan stability index curve (TSI curve) was used to evaluate the dispersion stability of J-SiQDs.

[0063] We designed and prepared amphiphilic J-SiQDs with high interfacial activity and dispersion stability. While maintaining high interfacial activity, the agglomeration rate is greatly reduced. J-SiQDs can remain monodispersed in water for a long time. First, the MSD curves of SiQDs and amphiphilic J-SiQDs were measured in aqueous solution using an optical microrheometer to reflect the migration area of ​​SiQDs and J-SiQDs within a certain period of time, and the quantitative characterization of the degree of violent movement was achieved by optical means. The MSD curve of SiQDs is shown in Figure 2. Figure 4 As shown in a, the area of ​​SiQDs migration within 1 second is reduced from the initial 58nm to 2 Reduced to 53nm 2 ,MSD values ​​are always in the lower range. Figure 4 The MSD curve of amphiphilic J-SiQDs is shown in Figure b. The area of ​​J-SiQDs moving within 1 s is from 149 nm to 2 Reduced to 119nm 2The intensity of the Brownian motion of J-SiQDs is about 3 times that of SiQDs, which is mainly caused by the different wettability of water on different hemispheres of J-SiQDs. This finding significantly supports that amphiphilic J-SiQDs exhibit stronger spontaneous adsorption performance at the oil-water interface. The MSD curve of amphiphilic J-SiQDs decreased significantly within 2 h, which is mainly due to the formation of a dense adsorption film on the water surface and interface climbing, resulting in a decrease in the effective concentration of J-SiQDs in the water phase.

[0064] In addition, the dispersion stability of SiQDs and J-SiQDs was evaluated by particle size measurement and TSI curve calculation in a multiple light scattering instrument to characterize their dispersion and stability. Figure 4 Figure c shows the particle size measurement results of 0.1wt% J-SiQDs after 48 hours. The average particle size of J-SiQDs increased from 4nm to 6nm, and Janus silicon quantum dots also showed excellent dispersion and stability. TSI data is shown in Figure 5. Figure 4 As shown in Figure d, it can be seen that the stability of J-SiQDs is slightly lower than that of SiQDs, but the TSI value of J-SiQDs is always in a lower range (<1), which indicates that J-SiQDs have good dispersion stability.

[0065] In order to demonstrate the difference in particle size and dispersion stability between SiQDs and J-SiQDs, we used a multiple light scattering instrument to measure the change in the transmitted light intensity of colloidal quantum dots. From the perspective of transmitted light intensity, the transmitted light intensity of SiQDs is about 88%, while the transmitted light intensity of J-SiQDs is about 83%. The difference between the two quantum dots with the same mass concentration is mainly caused by the change in particle size. Figure 4 As can be seen in e and f, a larger particle diameter leads to a decrease in the intensity of the transmitted light. This result is consistent with the results of the particle size analysis. The changes in the intensity of the transmitted light of SiQDs and J-SiQDs are similar, indicating that the dispersion stability of SiQDs after half-face modification has not decreased significantly.

[0066] Example 4

[0067] The amphiphilic J-SiQDs exhibit strong interfacial activity mainly because of their structure, i.e., half of the surface is hydrophilic and the other half is hydrophobic. To ensure the dispersion stability of Janus nanoparticles, traditional methods include creating a uniform hydrophilic layer on their surface by adding surfactants or polymers in water. Another method is to increase the electrostatic repulsion of the hydrophilic surface to achieve a stable dispersion state. The development of a homogeneous hydrophilic structure hinders the Brownian motion of Janus nanoparticles in water and reduces their ability to spontaneously adsorb at the oil-water interface, which contradicts the goal of producing Janus nanoparticles. Due to the inevitable agglomeration between the hydrophobic and hydrophilic surfaces, the increased electrostatic repulsion of the hydrophilic surface limits its effectiveness in maintaining the dispersion stability of the amphiphilic structure.

[0068] By grafting polyoxyethylene chains and polyoxypropylene chains onto the hydrophilic and hydrophobic halves of J-SiQDs, respectively, the compatibility of high interfacial activity and dispersion stability is achieved. The dispersion stability mechanism of J-SiQDs in water is as follows: Figure 5 As shown. Both polyoxyethylene and polyoxypropylene segments can form hydrogen bonds with water molecules in the water, forming a hydration layer on the surface, which can effectively prevent the particles from agglomerating ( Figure 5 (a). However, when the polyoxypropylene segment comes into contact with the oil phase, the interaction between the polyoxypropylene and the oil phase exceeds the hydrogen bonds formed between the oxygen atoms in the segment and the water molecules. Therefore, it will spontaneously adsorb at the oil-water interface, thereby improving its performance ( Figure 5 In addition, J-SiQDs have an uncharged surface and form a stable spatial structure with the organic chain segments. This makes them suitable for storage even under harsh environmental conditions (including Ca 2+ The concentration is 50000mg / L, the temperature is 120℃, the pH range is 4-10, and the particle concentration is 0.005-3.0wt%). The results of the relevant experiments are shown in Figure 8 .

[0069] Example 5

[0070] In order to further verify the dispersion stability mechanism of J-SiQDs and the adsorption performance at the oil-water interface, the dispersion stability phenomenon of J-SiQDs and the spontaneous adsorption at the oil-water interface were studied by molecular simulation. First, the stable state of J-SiQDs in water was simulated. The simulation process took 2ns and the time step was 2fs. The molecular simulation results are shown in Figure 2. Figure 6 As shown in (a). The hydrophobic organic chain shrinks in aqueous solution. By tracking the S atoms on J-SiQDs (only present in the hydrophobic organic chain) ( Figure 6In b), it was found that as the organic chain shrinks, J-SiQDs still show the characteristics of half hydrophilic and half hydrophobic. In order to verify whether J-SiQDs stably dispersed in water have the ability to spontaneously adsorb at the oil-water interface, molecular simulation of the adsorption process at the interface was performed. The simulation process was 3ns and the time step was 2fs. The results are shown in Figure 6 As shown in Figure c. When J-SiQDs come into contact with the oil phase, they are adsorbed to the oil-water interface due to their surface structure. This is because the hydrophobic interaction between the oil phase and the polypropylene segment is stronger than the hydrogen bonding interaction between the oxygen atoms in the polypropylene segment and the water phase. The interfacial activity will not be reduced by its stable dispersion in water. Subsequently, the mutual collision law of Janus silicon quantum dots when stably dispersed in water was verified. The experimental results are shown in Figure 6 As shown in 6d and 6e. Due to the large specific surface area of ​​J-SiQDs in the aqueous phase, they tend to agglomerate with each other to reduce the surface energy. In order to maintain the monodispersity of J-SiQDs, the particles are separated at a distance of about 2.75nm due to the mutual repulsion of the hydrophobic and hydrophilic parts (the oxygen atoms in the two segments prefer to form hydrogen bonds with water rather than with themselves). This further confirms that J-SiQDs have obtained a stable monodispersity that conforms to the Janus structure.

[0071] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for preparing Janus silicon quantum dots, comprising the following steps: 1) First, a strong reducing agent is added to deionized water, stirred to dissolve, a silicon source containing polyethylene glycol is added, stirred to mix, an alkali solution is added to adjust the pH of the mixture to 8-8.5, the resulting mixture is reacted at 100-120° C. for not less than 6 h, the product is dialyzed using a dialysis bag, and the resulting silicon quantum dot dispersion is evaporated and concentrated at high temperature to obtain a dispersion of silicon quantum dots containing polyethylene oxide segments on the surface; 2) mixing the obtained dispersion of silicon quantum dots containing polyoxyethylene segments on the surface with molten paraffin in water at a volume ratio of 8-12:1 and stirring to obtain small paraffin balls coated with silicon quantum dots; wherein, Half of the silicon quantum dot's surface is in contact with the small paraffin ball, and the other half is exposed; 3) First adjust the pH value of the solution to 3.5 ~ 4.5, add polypropylene glycol to the solution, and add bis-(3-(triethoxysilane)propyl)-disulfide dropwise while stirring. This process lasts for 3 hours. After the addition is completed, continue to react for 6-12 hours under stirring. After the reaction is completed, add a CaCl2 solution with a concentration of >30000 mg / L, and heat to 120℃ and boil for more than 3 hours to fully precipitate the paraffin from the water to achieve the removal of the paraffin; 4) dialyzing the system after removing the paraffin to obtain a Janus silicon quantum dot dispersion; In step 1), the mass volume ratio of the base to the silicon source containing polyethylene glycol is: 2.5-4 g: 10 ml; The silicon source containing polyethylene glycol is selected from: polyethylene glycol trimethoxysilyl propyl ether, polyethylene glycol triethoxysilyl propyl ether; The strong reducing agent is selected from: sodium citrate or sodium ascorbate; The alkali is selected from sodium hydroxide, potassium hydroxide or calcium hydroxide.

2. The preparation method according to claim 1, characterized in that: In step 1), the dialysis is performed for at least 48 hours; The mass concentration of silicon quantum dots containing polyoxyethylene chain segments on the surface in the obtained dispersion of silicon quantum dots containing polyoxyethylene chain segments on the surface is 10-20wt%.

3. The preparation method according to claim 1, characterized in that: In step 2), the stirring conditions are: stirring speed is 10000-12000 rpm, and stirring time is 5-15 min.

4. The preparation method according to claim 1, characterized in that: In step 3), the Mw of the polypropylene glycol is 600-1000; The mass volume ratio of polypropylene glycol, bis-(3-(triethoxysilyl)propyl)-disulfide and the silicon source containing polyethylene glycol in step 1) is: 2-5 g: 1-2 g: 10-12 ml; The volume ratio of the CaCl2 solution to the molten paraffin in step 2) is 20-100 ml:5 ml.

5. The preparation method according to claim 1, characterized in that: Step 4) During the dialysis process, the water was changed every 2 hours for the first three times, and then every 6 hours for 48 hours to obtain a pure Janus silicon quantum dot dispersion.

6. Janus silicon quantum dots prepared by the preparation method described in any one of claims 1 to 5.

7. The Janus silicon quantum dot according to claim 6, characterized in that The particle size of the Janus silicon quantum dots is below 10 nm.

Citation Information

Patent Citations

  • Method for preparing fluorine-doped fluorescent silicon quantum dots by microwave process

    CN105969346A

  • Amphiphilic Janus nano-particles with CO2 response performance and preparation method and application of amphiphilic Janus nano-particles

    CN117660023A

Cited By

  • Temperature and pH dual-responsive oil displacement agent, preparation method and application thereof

    CN122503103A